Managing public value through innovative mechanisms for financing sports infrastructure development: challenges and opportunities for Ukraine - Dunayev, Igor; Kushnir, Volodymyr (Theory and Practice of Public Administration, 2024)
This article tackles the pressing issue of managing societal value through innovative financing mechanisms for sports infrastructure development in the context of Ukraine’s post-war reconstruction. The main idea is to critically present these innovative financing mechanisms, comparing their potential with the risks posed by public administration dysfunctions in Ukraine and globally. The authors analyze worldwide trends and models in sports financing, focusing on the growing role of public-private partnerships, “greening,” and digitalization of the industry. At the same time, they uncover institutional challenges and implementation risks in the Ukrainian context, stemming from decision-making opacity, lack of cross-sectoral coordination, and underestimation of the social role of sports. A comparative analysis of European and Ukrainian contexts allows identifying common systemic barriers to effective and inclusive investment, as well as specific «pain points» of the domestic governance system. On this basis, adaptive mechanisms for introducing innovations in sports infrastructure financing are proposed, with an emphasis on developing public-private partnerships, crowdfunding, impact investing, and collaborative ecosystems at the local level. The article underscores the pivotal role of transparent, inclusive, and accountable governance mechanisms in ensuring that sports investments generate tangible societal benefits. It also highlights the potential of innovative financing tools, such as blockchain-based crowdinvesting platforms and social impact bonds, to democratize access to sports infrastructure financing while fostering community engagement. The authors argue that unlocking the industry’s investment potential requires not only attracting additional resources but also a fundamental transformation of stakeholder interaction principles towards greater accountability, inclusion, and focus on societal value. Only with such a holistic approach can sports infrastructure become a driver of post-war recovery and sustainable human development in Ukraine.